Importance of Imamzadeh Monument in Research of the Traditional Architectural Styles of Ganja - Hasanov, Elnur (Scholarya Demo Journal of Ruby, 2019)
Historical significance of the medieval monument Imamzadeh Mosque Complex as an important source in the study of ancient architectural features of Ganja, one of the ancient scientific and cultural centers of our country, was studied in this research. Imamzadeh mosque, the main and ancient historical monument of Muslim East civilization, is situated 7 kilometres from the city of Ganja, on the right shore of Ganjachai river. It is recognized as one of the basic symbols of the city and located in the territory of Ganja State Historical and Cultural Reserve. Ganja Imamzadeh Complex was built in 739, around the grave of Ibrahim, son of the fifth muslim imam Muhammed Bagir. Significant historical sources such as epitaphs and stone inscriptions were found in the territory of the monument. Imamzadeh Mosque Complex was completely built in the late 14th and early 15th century. However, in the 17th and 18th centuries, a mosque, several temples and other constructions were built around the monument. During the centuries many visitors, guests from different parts of Azerbaijan, also from the other muslim countries visited Ganja Imamzadeh monument. In the 19th century this historical complex was repaired by the Ganja commander Javad khan, but then in 1878-1879 years by major-general of the second muslim-cavalry regiment of Russian army Israfil bay Yadigarzadeh. President of the Azerbaijan Republic Mr. Ilham Aliyev signed the orders about the restoration and repair of Imamzadeh Mosque Complex based on local national architectural and constructive traditions. This article investigates the importance of this historical monument in the study of centuries-old local architectural styles of the city on the basis of scientific sources, samples of material culture and stone books (epigraphic samples).